ANALISIS DAYA TAMPUNG SEPTIC TANK TYPE KOMUNAL DI KELURAHAN TEGAL GUNDIL KOTA BOGOR - Ari Apriyana; Paikun; Bambang Jatmika (Jurnal TESLINK : Teknik Sipil dan Lingkungan, 2019)
Communal wastewater treatment plants (IPALs) are one of the solutions for dense urban or coastal environments. This research was conducted with Primary Methods and Secondary Methods. This research focuses on calculating capacity and calculating the budget for making communal septic tanks (RAB). Sample research was carried out at Kp Kawung Luwuk Rt 05 / Rw 01 Tegal Gundil Village, North Bogor District. The design of building a Communal Septic Tank (WWTP) with a drainage time of 2 years. The increase in the population of 5 years is 1.6% so the number of users of communal septic tanks totaling P (2020) is 355 people. WWTP is built with a tub volume of 61 m3 / day and the volume of accommodated waste is 28.4 m3 / day. The need for reservoir capacity for sludge (A) is 28,400 liters = 28.5 m3. The need for a minimum holding time in one day (Th) is 1,434 liters / person / day. The need for water storage capacity (B) is 5,094 liters = 5.1 m3.